2009
DOI: 10.1007/s11747-009-0140-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of employee behavior on brand personality impressions and brand attitudes

Abstract: This research examines how consumers update their brand personality impressions and brand attitudes after interacting with one of the brand's employees. Drawing on stereotyping theory, the author develops a framework that proposes that the impact of an employee's behavior depends on how the employee is categorized. When the employee is considered primarily as an exemplar of the brand's workforce, his or her behavior is generalized more strongly to the brand. When, however, the employee is judged as a relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 36 publications
(57 reference statements)
2
59
0
3
Order By: Relevance
“…Another manifestation of brand behavior (i.e., indexical cue) consists in behavior of employees who represent the brand. Employees who deliver on a brand's promise are important for a brand's success (Henkel, Tomczak, Heitmann, & Herrmann, 2007;Punjaisri & Wilson, 2007;Wentzel, 2009). If promises made in a brand's communication activities are not kept along all consumer-brand touch points, the brand's credibility decreases (Burmann & Zeplin, 2005).…”
Section: Antecedents Of Pba Dimensionsmentioning
confidence: 99%
“…Another manifestation of brand behavior (i.e., indexical cue) consists in behavior of employees who represent the brand. Employees who deliver on a brand's promise are important for a brand's success (Henkel, Tomczak, Heitmann, & Herrmann, 2007;Punjaisri & Wilson, 2007;Wentzel, 2009). If promises made in a brand's communication activities are not kept along all consumer-brand touch points, the brand's credibility decreases (Burmann & Zeplin, 2005).…”
Section: Antecedents Of Pba Dimensionsmentioning
confidence: 99%
“…Although being prototypical might be beneficial for the individual frontline employee when customers predominantly associate positive attributes with the organization (cf. Wentzel, 2009), prototypicality will likely be harmful when the organization is stigmatized, prototypicality will render the stigma psychologically salient to both the employee and the customer during the encounter. The more prototypical that frontline employee is for a specific organization, the more they quintessentially represent what the organization stands for and as a result, the more they are judged on the basis of their organizational affiliation.…”
Section: Stigmatization and Prototypicality For A Stigmatized Categorymentioning
confidence: 99%
“…Other research reported in the service marketing literature has addressed such aspects of the employee communication style, and its effects on customer evaluation, as employees' non-verbal communication (Hennig-Thurau, Groth, Paul, and Gremler, 2006); 'adaptive selling' and customer orientation (Bettencourt & Gwinner, 1996;Sparks, Bradley, & Callan, 1997); employee satisfaction (Hartline & Ferrell, 1996;Homburg & Stock, 2004); and customer perception of employee effort (Mohr & Bittner, 1995;Specht, Fichtel, & Meyer, 2007). Beyond the services marketing literature, Wentzel (2009) has analyzed the effects of different facets of employee communication on consumer's perceptions of brand image and attitudes to the brand in various product categories. All studies in this research stream underpin the relevance of interpersonal communication between employees and customers to successful branding, and hence, to the importance of internal brand equity in general.…”
Section: Personal Communicationmentioning
confidence: 99%